1986
DOI: 10.1002/jmv.1890180211
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackie B virus‐specific IgM responses in coronary care unit patients

Abstract: An enzyme-linked immunosorbent assay (ELISA) test using polyvalent antigens and antisera was used to detect Coxsackie B virus-specific IgM responses in 329 patients admitted to the Coronary Care Unit, Wellington Hospital, New Zealand over a 12-month period. The sera of 30 of 153 (19.6%) patients with acute myocardial infarction (AMI), 16 of 98 (18.4%) with chest pain, and 7 of 46 (15.2%) patients with arrhythmia were positive for Coxsackie B virus-specific IgM. Four of 12 (25%) patients with heart failure were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The warmer months of summer and au tumn appear to be favorable to coxsackie B viruses infections [2], Direct or indirect fecal-oral transmission is considered the most common mode of spread. Sewagecontaminated water, contaminated food, or insect vectors may occasionally be the source of infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The warmer months of summer and au tumn appear to be favorable to coxsackie B viruses infections [2], Direct or indirect fecal-oral transmission is considered the most common mode of spread. Sewagecontaminated water, contaminated food, or insect vectors may occasionally be the source of infection.…”
Section: Discussionmentioning
confidence: 99%
“…These specific IgM antibodies detected by Elisa test reach their peak titers in 2-3 weeks and thereafter decline to undetectable lev els [12,13]. Their presence is indicative of a current or recent antigenic stimulus [2], On the contrary, specific IgG antibod ies begin to rise on the 15th day, reach a peak after the first month and then tend to remain elevated for months [13,14]. The specificity of IgG antibody detection methods varies greatly according to which one is used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, CV-B are able to potentiate inflammation as well as cholesterol accumulation in mouse heart and aorta (Burch, 1975;Campbell et al, 1978;Illback et al, 1990). Third, seroepidemiologic studies have reported that recent enteroviral infection could precede myocardial infarction (Lau, 1986;Nicholls and Thomas, 1977;Roivainen et al, 1998;Wood et al, 1978). Fourth, enteroviral antigen, as well as RNA, has been detected in some vascular tissue of humans who died of infarction (Burch et al, 1973;Calabrese et al, 2003).…”
Section: Introductionmentioning
confidence: 95%